2012
DOI: 10.5812/iranjradiol.8465
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Ultrasound in Determining the Cause of Bilious Vomiting in Neonates

Abstract: BackgroundPlain radiography and contrast radiologic studies are traditionally the main options in evaluating neonates presenting with bilious vomiting. While ultrasonography (US) is more available, its diagnostic accuracy is in question.ObjectivesThe purpose of this study is to determine the diagnostic accuracy of US in evaluating these patients with bilious vomiting.Patients and MethodsAll neonates with bilious vomiting or bilious nasogastric tube drainage presented to a children’s hospital in a 1.5-year peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 12 publications
1
16
0
1
Order By: Relevance
“…In the past, upper gastrointestinal examination was the preferred examination for the diagnosis of intestinal malrotation, although it had the drawbacks of low sensitivity, radiation exposure, and difficult positioning. [ 9 ] In addition, Barium enema is no longer a routinely used diagnostic method for malrotation due to the fact that approximately 20% of children with malrotation have a normally positioned cecum. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, upper gastrointestinal examination was the preferred examination for the diagnosis of intestinal malrotation, although it had the drawbacks of low sensitivity, radiation exposure, and difficult positioning. [ 9 ] In addition, Barium enema is no longer a routinely used diagnostic method for malrotation due to the fact that approximately 20% of children with malrotation have a normally positioned cecum. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…The main advantages of ultrasound are noninvasiveness and simplicity. [ 13 ] Alehossein et al [ 9 ] reported that sonographic accuracy eliminated the need for further diagnostic tests. In this study, 6 patients with other diseases were also successfully detected by ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of babies requiring surgical interventions was similar to a UK study reported by Godbole (38%) and Kao (51.1%) from Taiwan, whereas a North-American study from a tertiary neonatal unit and an Australian study have reported lower rates of 20% and 26.6%, respectively. An Iranian study by Alehossein et al 11 reported a series of 23 babies admitted over an 18-month period to a children's hospital with bilious vomiting where 18 (78.3%) had a surgical diagnosis. These differences in likelihood of surgical diagnosis in neonates with bilious vomiting may reflect variation in practices and thresholds for further investigation and referral.…”
Section: Discussionmentioning
confidence: 99%
“…У наших дослідженнях також був виявлений симптом «виру» (рис. 3), проте без ознак завороту під час хірургічного втручання, що підтверджують й інші дослідники [1].…”
Section: обговоренняunclassified